Security implications of ICT adoption in the High Courts of Malaysia - Mohamad, Ani Munirah; Hamin, Zaiton; Othman, Bahrin (International Association of Computer Science and Information Technology Press (IACSIT), 2012)
Bearing in mind the double-edged nature of information and communication technology (ICT), it is admitted that at one end, ICT introduces great possibilities and benefits, at the other end, it inevitably leads to various uncertainties and insecurities.It is within this context that this paper aims to critically examine the security implications of ICT in the High Courts of Malaysia.In addition, this research aims to propose recommendations for the amendment to the relevant statutes, improvement to the practice directions and to propose best practices and code of conduct in implementing ICT in the courts.Drawn from an ongoing research which attempts to examine the legal implications of the current adoption of ICT on the delivery of the civil justice system of the High Courts in Malaysia, the research adopts s qualitative method, comprising of the collection of primary data (which involves a field work adopting the case study design) and secondary data (which involves a library-based research).The primary data which have been generated is analysed by using the computer-aided qualitative data analysis software ATLAS.ti version 6.2 prior to reporting of the same.The paper concludes that the adoption of ICY in these courts are imbued with numerous security implications, which in many ways would challenge the way the judicial business would be carried out and also the way in which justice would he delivered and served.